Mathematical communication skills of students in agricultural-based regions: Proficiency levels, challenges, and instructional strategies - Salido, Achmad; Kausar, Aufal; Aswin, Aswin; Marniati, Marniati (Mahesa Research Center, 2025)
Mathematical communication is a fundamental skill that enables students to express and justify mathematical ideas clearly. This study examines students’ mathematical communication skills in an agricultural-based region, focusing on proficiency levels and influencing factors. Using a qualitative case study approach, data were collected from 21 eighth-grade students through problem-solving tasks assessing three key indicators: mathematical modeling, explanation of mathematical patterns, and question formulation. The results indicate that most students exhibit moderate mathematical communication abilities, with only a small proportion demonstrating high proficiency. High-ability students effectively integrate multiple representations and justify their reasoning, while moderate-ability students rely on procedural approaches with limited conceptual depth. Low-ability students face significant challenges in constructing mathematical models and articulating solutions. These findings suggest that contextual factors, including limited access to quality education and instructional strategies, impact students' mathematical communication development. Although students in agricultural communities engage with quantitative reasoning in real-life contexts, they struggle to translate these experiences into formal mathematical communication. The study highlights the need for differentiated instructional strategies, including explicit reasoning exercises and contextualized learning, to enhance students’ communication skills. However, the study’s limited scope and sample size necessitate further research across diverse regions to explore long-term interventions. Future studies should investigate culturally relevant pedagogical approaches to strengthen mathematical communication, particularly for students in rural and agricultural settings.